The role of adiponectin receptors in the regulation of synaptic transmission in the hippocampus. Issue 5 (21st February 2017) - Weisz, Filippo; Piccinin, Sonia; Mango, Dalila; Ngomba, Richard Teke; Mercuri, Nicola B.; Nicoletti, Ferdinando; Nisticò, Robert
Abstract: In the last two decades adiponectin, member of the adipokines family, gained attention because of its unique antidiabetic effects. However, the presence in the brain of adiponectin receptors and adiponectin itself raised interest because of the possible association with neuropsychiatric diseases. Indeed, clinical studies found altered concentration of adiponectin both in plasma and cerebrospinal fluid in several pathologies including depression, multiple sclerosis, Alzheimer's disease and stroke. Moreover, recent preclinical studies also suggest its involvement in different physiological functions. Despite this evidence very few studies attempted to elucidate the functional role of adiponectin at the synapse. To address this question, here we investigated the effect of Adiporon, an agonist of both adiponectin receptors on synaptic transmission and LTP at Schaffer‐collateral CA1 pathway. Surprisingly, increasing concentration of Adiporon correlated with lower CA1–LTP levels and paired‐pulse ratio, whereas basal transmission was always preserved. Collectively, our data show that the adiponectin system, beyond its involvement in metabolic diseases, plays also a critical role in synaptic activity thereby representing a putative target for the treatment of synaptic pathologies. Abstract : Utilizing fEPSP recording in hippocampal slices the authors showed that adiponectin receptors activation led to a dose‐dependent dampening of LTP. Adiporon had no effect on basal evoked synaptic transmission but it decreased the paired pulse facilitation and the responses during high frequency stimulation. A reduction of AMPA receptor‐mediated current is probably involved in the latter effect.